Boron-doped silver nanosponges with enhanced performance towards electrocatalytic nitrogen reduction to ammonia. Issue 98 (22nd November 2019) - Li, Yinghao; Yu, Hongjie; Wang, Ziqiang; Liu, Songliang; Xu, You; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract : Boron-doped silver nanosponges synthesized from a one-step method exhibit superior performance for the electrocatalytic nitrogen reduction reaction. Abstract : In this communication, we develop a simple one-step method to prepare boron doped silver nanosponges (B–Ag NSs) with a boron content of 15 at%. Benefiting from their interconnected porous structures and composition effect, the B–Ag NSs achieve excellent NRR performance and stability. The proposed synthetic strategy provides promising insight into the preparation of boron doped metallic nanomaterials for electrocatalytic fields.